1970
DOI: 10.1111/j.1600-0722.1970.tb02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal epithelial hyperplasia of the oral mucosa in a south‐west Greenlandic population

Abstract: Abstract— Focal epithelial hyperplasia of the oral mucosa was found in 19.4% of 460 inhabitants of an Eskimo population in south‐west Greenland (Nanortalik). The condition was found in all age groups examined, the youngest person with focal epithelial hyperplasia being 2 years old, the oldest 70 years old. There was a statistically significant higher prevalence (33.1%) in the age group above 30 years old than in the age group below 30 years old (14.3%). No significant difference in prevalence could be found be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

1973
1973
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…2,4,6,17,18,29,30 The time course of the disease is difficult to establish, since the lesions are usually asymptomatic 7 ; however, in this study, evolution time ranged from 1 month to 34 years. In other reports, evolution time usually ranged from a few months, or even weeks, to a few years.…”
Section: Commentmentioning
confidence: 97%
“…2,4,6,17,18,29,30 The time course of the disease is difficult to establish, since the lesions are usually asymptomatic 7 ; however, in this study, evolution time ranged from 1 month to 34 years. In other reports, evolution time usually ranged from a few months, or even weeks, to a few years.…”
Section: Commentmentioning
confidence: 97%
“…In American Indians the hyperplasias have predominantly been found in children between 3 and 18 years [12-14, 16, 39, 43] although they have been observed in grown-up persons as well [11,26], In Eskimos the dis order has been found in all age groups and the highest prevalences have been found in the age groups above 30 years [9]. Some investigators have found differences in the prevalence among the two sexes [3], others have not [9], The predominating locations of the lesions in American Indians have been [16] -in order of frequency -mucosa of the lower lip, buccal mucosa, commissures, and labial mucosa of the upper lip.…”
mentioning
confidence: 99%
“…Some investigators have found differences in the prevalence among the two sexes [3], others have not [9], The predominating locations of the lesions in American Indians have been [16] -in order of frequency -mucosa of the lower lip, buccal mucosa, commissures, and labial mucosa of the upper lip. In Eskimos [9], however, more than 50% of the lesions are located to the tongue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in contrast to previous studies, they found that the disease could also appear in adults, with an overall age range of 2 to 79 years, and that more than 50% of lesions were localized on the tongue (49). In a similar study, Henke et al found no significant gender or age differences and confirmed the possible presence of the disease in adults, reporting an age range for sufferers of 22 to 85 years (50).…”
Section: Findings Pertaining To Multifocal Epithelial Hyperplasiamentioning
confidence: 71%